2011
DOI: 10.1007/s12507-011-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

“Dan blijf ik gewoon stil”: ervaringen van allochtone studenten met interculturalisatie tijdens de opleiding Geneeskunde

Abstract: InleidingDe afgelopen jaren is de etnische en culturele diversiteit in Nederland sterk toegenomen. In 2010 werd 20% van de bevolking als allochtoon ('zelf of ten minste één ouder niet in Nederland geboren', definitie CBS -meestal worden hier op de eerste plaats 'niet-westerse allochtonen' bedoeld) beschouwd. Geneeskunde. Tijdschrift voor Medisch Onderwijs 2011:30(6):292-301.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Third, since students’ acceptance of knowledge about diversity as useful for practice negotiates the degree to which diversity issues are considered legitimate by faculty staff, teachers and peers, they can be considered active stakeholders in the process toward a diversity-responsive curriculum. Therefore, parallel to Phase 1 of this study, another study was carried out that explored medical students’ experiences with diversity issues within the VUmc SMS curriculum, results of which were reported in a Dutch language paper (Tjitra et al 2011 ). The authors of the paper reported that students with a minority background experienced a lack of respect in the way they were treated by peers and teachers (for instance during modules on physical examination), and that these students felt that patient cases used to teach about specific health issues of minority groups were stigmatising and stereotypical (Tjitra et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, since students’ acceptance of knowledge about diversity as useful for practice negotiates the degree to which diversity issues are considered legitimate by faculty staff, teachers and peers, they can be considered active stakeholders in the process toward a diversity-responsive curriculum. Therefore, parallel to Phase 1 of this study, another study was carried out that explored medical students’ experiences with diversity issues within the VUmc SMS curriculum, results of which were reported in a Dutch language paper (Tjitra et al 2011 ). The authors of the paper reported that students with a minority background experienced a lack of respect in the way they were treated by peers and teachers (for instance during modules on physical examination), and that these students felt that patient cases used to teach about specific health issues of minority groups were stigmatising and stereotypical (Tjitra et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, parallel to Phase 1 of this study, another study was carried out that explored medical students’ experiences with diversity issues within the VUmc SMS curriculum, results of which were reported in a Dutch language paper (Tjitra et al 2011 ). The authors of the paper reported that students with a minority background experienced a lack of respect in the way they were treated by peers and teachers (for instance during modules on physical examination), and that these students felt that patient cases used to teach about specific health issues of minority groups were stigmatising and stereotypical (Tjitra et al 2011 ). As this provided us with insight in the student perspective, we chose not to interview students as part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The higher grades achieved by women in comparison with men are not reflected in their career progress, nor in their influx into several specialties, counter to the principle of merit the medical profession claims to embrace. Ethnic minority medical students and young minority specialists in training do not ‘feel at home’ and perceive a systematic underestimation of their capacities, reporting: ‘I have seen how as an ethnic minority student you actually already have a particular disadvantage […] You have to catch up.’ Their experiences are in line with the remarks of Muzzin and Mickleborough about the mainstream study in which the structural disadvantages experienced by internationally trained doctors are individualised and how their sense of not being able to ‘catch up’ is framed as a character flaw. But against whose norms are they being pushed to ‘catch up’?…”
mentioning
confidence: 99%
“… 4 Little data, however, have been published with regard to how ethnic minority students experience their social and learning environment in medical school. 5 The few published data show a consistent picture, though; ethnic minority students perceive that their capacities are systematically underestimated and that their ethnicity negatively affects their social learning experiences, 6 such as a sense of belonging. 7 This study tests whether potential differences in social learning experiences between ethnic minority and majority students affect students' ‘self‐regulatory focus’, a psychological concept used to describe how people orientate themselves towards goals.…”
Section: Introductionmentioning
confidence: 99%
“…Three social learning experiences of medical students are specified in this study, namely; the extent to which students (a) perceive they are treated unfairly, 9 (b) have trust 10 in their clinical supervisors and (c) feel a social academic fit 4 in clinical training. It is expected that ethnic minority students have more negative social learning experiences, because they are at a greater risk to receive lower grades 11 , 12 , 13 and insufficient support 5 and to experience negative effects of stereotypes and discrimination by supervisors and peers, 5 , 6 , 14 , 15 as compared with ethnic majority students. More specifically, perceptions of unfair treatment could come from implicit criteria that are associated with professionalism, which may be harder to meet for ethnic minority students (as stated by minority respondents).…”
Section: Introductionmentioning
confidence: 99%